Pengembangan Dashboard Data Akademik Berbasis Web untuk Monitoring Siswa dan Guru di SMA Negeri 1 Tanjung Bintang - Robin Abednego Sudibyo; Nursiyanto Nursiyanto (Universitas Bandar Lampung (UBL), 2026)
ABSTRACT – The management of academic data, including student data, teacher data, attendance, and grades, is anessential aspect of supporting effective school administration. However, in practice, academic data are often storedin separate systems, making it difficult for schools to monitor information and make decisions quickly and accurately.This study aims to develop a web-based academic data dashboard that presents integrated and easily accessibleacademic information at SMA Negeri 1 Tanjung Bintang. The system was developed using the waterfall method,which consists of requirements analysis, system design, implementation, and testing stages. The developed dashboardpresents key academic information, including student data, teacher data, attendance, and grades, through informativevisualizations. The results indicate that the web-based academic data dashboard facilitates academic monitoring andimproves the efficiency of academic data management to support decision-making processes.